National Divergences in Perinatal Palliative Care Guidelines and Training in Tertiary NICUs - Boan Pion, Antonio; Baenziger, Julia; Fauchère, Jean-Claude; Gubler, Deborah; Hendriks, Manya J. (Frontiers in Pediatrics, 2021)
Objectives: Despite established principles of perinatal palliative care (PnPC), implementation into practice has shown inconsistencies. The aim of this study was to assess PnPC services, examine healthcare professionals (HCPs) awareness and availability of PnPC guidelines, and describe HCPs satisfaction with PC and guidelines. Material and methods: A nationwide survey was conducted in Swiss tertiary NICUs between April-November 2019. Data were examined by descriptive statistics and linear regression models. Results: Overall response rate was 54% (65% physicians; 49% nurses; 72% psychosocial staff). Half of professionals (50%) received education in PC during their medical/nursing school, whereas 36% indicated they obtained further training in PnPC at their center. PnPC guidelines were available in 4/9 centers, with 68% HCPs being aware of the guideline. Professionals who had access to a PnPC team (P=.001) or were part of the nursing (P=.003) or psychosocial staff (P=.001) were more likely aware of having a guideline. Twenty-eight percent indicated being satisfied with PC in their center. Professionals with guideline awareness (P=.025), further training (P=.001), and access to a PnPC team (P<.001) were more likely to be satisfied, whereas HCPs with a nursing background (P <.001) were more likely to be dissatisfied. A majority expressed the need for a PnPC guideline (80%) and further PC training (94%). Conclusion: This study reveals lacking PnPC guidelines and divergences regarding onsite opportunities for continued training across Swiss level III NICUs. Extending PnPC guidelines and training services to all centers can help bridge the barriers created by fragmented practice.